Telaah Arsitektur Eklektik pada Bangunan Masjid Haji Keuchiek Leumiek - Foenna, Fala; Karsono, Bambang; Fidyati, Fidyati (Jurnal Etnik: Ekonomi-Teknik, 2023)
Indonesia is a country where the majority of the population is Muslim, especially Aceh. So it is not surprising that you can find many mosques with magnificent architecture and a great historical background. With globalization, many new architectural styles have emerged, for example eclectic architecture which influences the exterior and interior shapes of mosques. The application of eclectic architecture in the design process by adopting elements that are considered the best originating from local and non-local architecture so as to produce a building model that has its own charm and characteristics. One element of foreign architecture that is now being adopted domestically is Middle Eastern architecture. This phenomenon made researchers interested in conducting research on one of the mosques that displays Middle Eastern accents on its building facade, namely the Haji Keuchiek Leumiek Mosque, Banda Aceh. This research aims to reveal the eclectic aspects of the Haji Keuchiek Leumiek Mosque building, as well as which facade elements adopt Middle Eastern architecture. The method used to obtain data in this research is a comparative-qualitative method. Data collection techniques are carried out through observing the location of the study object, conducting interviews and documenting it in photographs, then comparing it with expert theories to reach conclusions. The results of the analysis show that the Haji Keuchiek Leumiek Mosque was built with characteristics of eclecticism. Middle Eastern architecture and various regional ornamental arts combine to create unique design aspects of the mosque. Awan Meucanek, Bungoeng Meulu, Bungoeng Putik, Sulur Oen Teube, Awan, and Bungong Geulima are examples of local ornaments in mosque architecture. The findings show that when compared with the remains of Islamic dynasties, the architecture of this Middle Eastern mosque is not exactly the same. However, in general, the architectural design of this mosque is very similar to mosques built during the Fatimid and Timurid periods.